Invisibility And Hypervisibility: Imagining Publics For Urban Broadband Networks - Halegoua, Germaine; Lingel, Jessa (AoIR Selected Papers of Internet Research, 2017)
Policies about internet access as a public good are not just about providing a resource, but about making that resource visible, usable and accessible. In our investigation of urban internet access projects as invisible versus hypervisible, we examine how imaginations of internet access and modes of infrastructure control critically reshape both the meaning of public and of connection. We approach the study of connectivity as a public good through the juxtaposition of “dark fiber” networks as inactive networks that are buried under the streets and have always been “turned off,” with activated networks (specifically LinkNYC in New York City) that are “turned on” and prominently displayed on city streets. These case studies highlight the shifting parameters of inclusion in both imagined urban communities and imagined internet publics. These debates are about two kinds of publics: who gets to use the internet and who gets to use the street, where the stakes involve thinking about what kinds of behaviors are viewed as appropriate, and whose uses will win as this technology stabilizes. Through an ethnographic and urban media archaeological analysis of hypervisible and invisible networks, this project investigates what is at stake in “our digital rights to the city” (Shaw & Graham, 2017). By analyzing LinkNYC as a public spectacle and dark fiber as buried potential, this paper re-envisions the street as a contentious space where the constitution of publics, both as civic and as internet users, are discerned and debated.